Two-arc-transitive two-valent digraphs of certain orders - Bercic, Katja; Potočnik, Primož (Ars Mathematica Contemporanea, 2016)
The topic of this paper is digraphs of in-valence and out-valence 2 that admit a 2-arctransitive group of automorphisms. We classify such digraphs that satisfy certain additional conditions on their order. In particular, a classification of those with order kp or kp(2) where k <= 14 and p is a prime can be deduced from the results of this paper.
Keywords: Graph; digraph; arc-transitive; order